Pembatalan Pesanan Pada Jual Beli Online Sistem Cash On Delivery (COD) Perspektif Hukum Ekonomi Syariah (Studi Kasus Pada Toko Online Sweeter Shop di Kecamatan Kalisat) - Mohammad Firmansyah; Nurul Izah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2021)
One of the advantages or advantages of online buying and selling activities with the current cash on delivery (cod) system is very helpful for everyone in terms of meeting all their needs. By only capitalizing on waiting for the order to arrive at home and being paid after the goods arrive at the hands of consumers. However, in addition to these positive things, there are also several risks arising from transactions using the cash on delivery (cod) system, one of which is canceling the order even though the goods have reached the consumer's address. This also happened in the online shop